Digital Transformation of the Management Information System (MIS) at Pondok AnNahdloh, Selangor, Malaysia - Nur Aini, Desti; Winarno, Agung; Yusniawati, Yusniawati; Rahman, Amalia Arifah (Technium Social Sciences Journal, 2023)
The role of information technology in enhancing institutional quality, particularly at Pondok AnNahdloh in Malaysia, cannot be underestimated. Information technology is vital in elevating an institution's standards by improving efficiency, communication, decision-making, security, and innovation. Institutions that effectively embrace information technology can optimize their operations and achieve higher levels of quality, resulting in enhanced competitiveness and desired outcomes. The research's primary objective is to describe the Education Management Information System (MIS) for educational documents at Pondok AnNahdloh in Malaysia, which is up-to-date and integrated. The research methodology involves focus group discussions to identify administrative activities, system application design, system testing, improvement, operator training, limited user testing, launching, and evaluation. Data collection methods include field observations, interviews, and activity documentation. Data analysis follows the theory of Miles and Huberman. The research findings reveal the successful implementation of MIS, leading to up-to-date and integrated educational document data, both in terms of input and processes. Adopting information technology in the academic environment through this system ensures efficient and accurate access, management, and utilization of essential data and information in the educational process. With this system in place, improvements in activity quality are expected, positively impacting community empowerment and national development.